Thin-Film Electrode-Based Supercapacitors - Yu, Minghao; Feng, Xinliang (Joule, 2019)
Thin-film electrodes (TFEs), which consist of a layer of active material with a thickness ranging from nanometers to micrometers, have been widely explored in the field of supercapacitors (SCs)—especially thin-film SCs, flexible and/or stretchable SCs, and microsupercapacitors (MSCs). Their unique configurations with thin and uniform thicknesses can not only guarantee fast electrochemical responses during charging and discharging but also allow TFEs to be used in portable and/or miniaturized devices. While extensive efforts have been directed toward the fabrication of TFE-based SCs, there are still several scientific and technological issues that remain unsolved. This perspective article first summarizes the active materials and electrolytes used for TFEs. According to the configurations and thicknesses of TFEs, we further analyze various electrode processing approaches with particular emphasis on electrochemical behavior. Recent discoveries regarding innovative device technologies based on TFEs (flexible/stretchable SCs and in-plane MSCs) are subsequently discussed. Finally, this perspective addresses exciting opportunities in exploring new materials; constructing hybrid SCs; and producing low-cost, large-scale, and eco-friendly TFEs for SCs.
CRIS-Team Scopus Importer:2023-03-20
Keywords: device technologies; electrode processing; material development; supercapacitors; thin-film electrodes